A Phase Readout Method for Wireless Passive Sensor Used in Pressure Measurement System. Issue 4 (1st October 2015) - Hong, Yingping; Liang, Ting; Zheng, Tingli; Zhang, Hairui; Liu, Wenyi
Abstract : A phase diﬀerence detection method used for reading the resonant frequency through mutual coupling is designed to meet the pressure measurement in harsh environments, and a testing device of integrated modular by developing the hardware circuits is proposed. Description and discussion of the novel theoretical model in the phase readout system is presented, and a pressure test platform based on the phase diﬀerence detection is also established, which is to measure the frequency of a LC resonant sensor on the basis of 96% alumina ceramic substrate. The experimental results show that the proposed phase diﬀerence readout system presents sweep‐frequency detection in the range of 1–100MHz bandwidth, and a high frequency resolution of 0.006MHz. Sensitivity of the sensor is approximately 0.225 MHz/bar from 1 bar to 2 bar. The accuracy and functionality of the phase readout system have emphasized a wider engineering application range, so that we can make it possible that the wireless passive LC resonant sensor revolves well in practical engineering occasions outside the laboratory environment.